Generalized Selection Multiuser Scheduling for the MIMO FSO Communication System and Its Performance Analysis - Min Qin; Li Chen; Weidong Wang (IEEE Photonics Journal, 2016)
This paper analyzes the impact of generalized selection multiuser scheduling on the performance of the multiple-input–multiple-output (MIMO) free-space optical (FSO) communication system. We consider a general scenario that the point-to-multipoint system consists of a central transmitter equipped with $K$ aperture groups containing $M$ transmit apertures and $K$ users equipped with $N$ receive apertures communicating over gamma–gamma turbulence FSO channels. For the MIMO links between the central node and user, we derive the combining signal-to-noise ratio (SNR) distributions of MIMO repetition coding and MIMO transmit laser selection. Then, a statistics analysis is presented for the multiuser diversity scheme in which the user with the $k$ th best combining SNR is selected. Based on the analysis, the closed-form expressions of the outage probability are derived, and the diversity benefit provided by the channel fluctuations is further discussed. Numerical results verify the accuracy of these analytical results.